Գարեգին Սրուանձտեանցը որպէս ստորին առասպելաբանական կերպարների մասին զրոյցների առաջին գրառող ու մեկնաբան - Գալստեան, Յասմիկ (տպ. Atlas)
Bishop Garegin Srvantsdztiants in his folk and ethnographic writings allocated a significant place to Armenian folk beliefs and prejudices. In the books he published, like Grots Oo Brots, Manana and Toros Aghbar, he repeatedly referred to folk stories about spirits, belief manifestations, rituals and customs. Srvantsdztiants was the first among the Armenian folklorists who did not disregard the beliefs and prejudices that existed among the people and constituted a part of the folk’s everyday life. He observed that "there are many superstitious stories and customs prevalent among the people, which long for recording and study." Based on his written materials, Srvantsdztiants gives the characteristics of the spirits and explains the origins, reasons and circumstances of these beliefs. Furthermore, by presenting specific tales, Srvantsdztiants highlights folk beliefs about mythological characters who lived in the lower world. Scattered throughout his writings are numerous references to superstitions, the evil eye, diseases and folk versions of their cures. Emphasizing the role of education among the common people, Srvantsdztiants attributes the variety of popular stories about spirits, living rooted beliefs and prejudices to the lack or complete absence of education among the people.
Keywords: Գրական վերլուծութիւն; Գարեգին Սրուանձտեանց